Spatial assessment of agricultural vulnerability in selected municipalities of Karnali Province, Nepal - Maharjan, Bishnu; Ghimire, Shiba Raj; Acharya, Pushpa Raj; Aryal, Kamal Prasad; Thakuri, Sudeep (Journal of Agriculture and Natural Resources, 2025)
This study evaluates Agricultural Vulnerability Indexing (AVI) across the selected municipalities of Karnali province of Nepal characterized by difficult terrain, fragile agricultural systems, and increasing climatic stresses. Using a geospatial approach, six indicators: land use and land cover (LULC), drainage conditions, slope stability, market availability, livestock suitability, and road accessibility were analysed at the ward level. Data were collected from multiple sources using a structured checklist for three municipalities: Simikot (Humla), Dullu (Dailekh), and Bheriganga (Surkhet). Each indicator has been categorized on a scale of 1 to 5 based on its contribution to overall vulnerability, and the AVI which was also normalized between 0 and 1 to generate composite vulnerability scores. The findings indicated that there was considerable spatial variation in vulnerability across the 34 assessed wards. As of result, Simikot-1 recorded a very high AVI exceeding 0.8, indicating the most vulnerable ward. Similarly, high vulnerability was also observed in Dullu (Wards 1, 8, 13), Simikot (Wards 4, 7, 8), and Bheriganga (Ward 13), while Dullu-4 and Bheriganga-7 exhibited the lowest AVI scores. Environmental limitations like unstable slopes, poor drainage, limited farmland, and socioeconomic challenges like weak infrastructure, low technology access, and poverty increase vulnerability; yet communities use traditional indigenous, community-based practices resiliently. The study highlights the value of geospatial and temporal analysis for identifying ward-specific vulnerabilities and informing evidence-based planning. The results offer practical guidance for prioritizing interventions and strengthening agricultural resilience and food security in Karnali Province.